Drylands becoming drier: evidence from North Patagonia, Argentina - Hurtado, Santiago Ignacio (2023)
In the last decades, Northern Patagonia (Argentina) has shown linear trends to drier conditions in distinct hydrological variables. Therefore, North Patagonia climate changes were studied using streamfow data of Neuquén and Chubut rivers, together with temperature and precipitation data. A climate shift around 2006–2008 towards warmer and drier conditions was identifed. A precipitation decline (~20%) was observed, being the main reduction in the early Austral winter (May–July). Consequently, a decrease in the streamfows of Chubut (27.8%) and Neuquén (40.3%) rivers was found for the 2007–2021 period, when compared to the 1980–2006 period. Most of the region recorded an increase of the mean temperature of at least 0.5 °C, leading to a greater water loss via evapotranspiration. Temperature changes were greater in the Austral summerautumn season (January-May) with warming up to 1.5 °C. After 2007, both rivers exhibited their second streamfow peak earlier, probably due to accelerated melting caused by the warmer conditions. This implies that the spring streamfow peak decreased earlier and might not be able to sustain the water demands in the summer-autumn, which should be the focus for water management adaptations.